Prognostic value of rest B-lines with the simplified 4-site scan for predicting survival: incremental value over transthoracic echocardiography. (3rd October 2022) - Merli, E; Ciampi, Q; Arbucci, R; Cortigiani, L; Zagatina, A; Wierzbowska-Drabik, K; Djordjevic-Dikic, A; Amor, M; Boshchenko, A; Rodriguez-Zanella, H; Barbieri, A; Haberka, M; et al.
Abstract: Background: Lung ultrasound (LUS) detects pulmonary congestion as B-lines at rest. Methods: After preliminary exclusion of 154 patients lost to follow-up, we analyzed transthoracic echocardiography (TTE) plus LUS (4-site simplified scan) data in 5165 subjects (age 64±11 years) referred to 19 certified centers of 9 countries for known or suspected coronary artery disease (n=3891, 75%), dyspnea (n=591, 12%), or screening in asymptomatic patients with risk factors (n=667, 13%). We analyzed the anterior and lateral hemi-thoraces, scanning from mid-axillary to mid-clavicular lines on the third intercostal space. B-lines score ranged from 0 (normal) to 40 (severely abnormal). By selection, follow-up information was available in all. All-cause death was the predetermined end-point. Results: Feasibility of B-lines was 100% in all subjects. B-lines (median) were 0.1 [0–1]. Rest B-lines (≥2) were present in 863 patients (16.7%). Ejection fraction was 61±10%. After a median follow-up of 690 (Interquartile range 420–1065) days, 96 all-cause deaths occurred. Two-year mortality was 3.6% in patients with and 1.5% in patients without B-lines (p<0.001) and increased progressively with the increasing number of B-lines, from 2.4% in mild (2–4, n=630), 5.0% in moderate (5–9, n=160) and 8.2% in patients with severe (≥10, n=73) B-lines (see figure). At multivariable analysis, rest B lines (HR 1.812, 95% CI: 1.165–2.916, p=0.008) and ejection fraction (HR 0.987, 95% CI: 0.976–0.998, p=0.020) were independent predictors of all-cause death, in addition to age (HR 1.045, 95% CI: 1.023–01.067, p<0.001) and diabetes (HR 1.643, 95% CI: 1.079–2.503, p=0.021). Conclusion: In all-comers referred for TTE, resting B-lines assessed by focused LUS with the simplified 4-site scan are detected in 1 out of 4 patients with symptos or coronary risk factors and are associated with worse survival. The severity of pulmonary congestion predicts the severity of outcomes. The prognostic value of resting B-lines is independent and additive over standard clinical and TTE predictors such as diabetes and ejection fraction. Focused LUS for pulmonary congestion can easily be incorporated in standard TTE examination. Funding Acknowledgement: Type of funding sources: None.